2020
DOI: 10.3389/fpsyg.2020.554061
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Metaphor Mapping of Moral Concepts in Chinese Culture

Abstract: According to conceptual metaphor theory, individuals are thought to understand or express abstract concepts by using referents in the physical world—right and left for moral and immoral, for example. In this research, we used a modified Stroop paradigm to explore how abstract moral concepts are metaphorically translated onto physical referents in Chinese culture using the Chinese language. We presented Chinese characters related to moral and immoral abstract concepts in either non-distorted or distorted positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…At the same time, some researchers found that people have a greater preference for straight lines after recalling moral events than they do after recalling immoral events [ 40 ]. Similar results were found in a semantic recognition task, where participants were asked to judge the moral properties contained in standard or distorted Chinese characters using the Stroop paradigm, and it was found that when presented with standard Chinese characters, participants were able to identify morally significant characters faster and more accurately, while when they were presented with distorted Chinese characters, they were able to identify characters with immoral meanings faster and more accurately [ 41 ].…”
Section: Discussionsupporting
confidence: 55%
“…At the same time, some researchers found that people have a greater preference for straight lines after recalling moral events than they do after recalling immoral events [ 40 ]. Similar results were found in a semantic recognition task, where participants were asked to judge the moral properties contained in standard or distorted Chinese characters using the Stroop paradigm, and it was found that when presented with standard Chinese characters, participants were able to identify morally significant characters faster and more accurately, while when they were presented with distorted Chinese characters, they were able to identify characters with immoral meanings faster and more accurately [ 41 ].…”
Section: Discussionsupporting
confidence: 55%
“…As metaphors have the quality that the attributes of one object are mapped onto the other, the same instances have been found in the selected companies' analysis (Freeman, 2000). The advertising agencies map the positive qualities of one thing or feeling to the products, which persuades them to think about the product as the companies want them to think (Liu et al, 2020). The analysis found that the products are associated with women empowerment, prosperous future, partner, ride, inspiration, feeling great, favor, Hawaii Island, journey, feeling good, and game.…”
Section: Discussionmentioning
confidence: 67%
“…It was consistent with the conventional view that interventions for L2 metaphorical competence are effective. Liu et al ( 2020 ) utilized a modified Stroop paradigm to study how Chinese culture metaphorically translates abstract moral notions into tangible referents. Chen et al ( 2018 ) also revealed that the source domain's relationship to the destination domain affects the development of metaphor.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 2018 ) also revealed that the source domain's relationship to the destination domain affects the development of metaphor. The study employed a variant of the Stroop paradigm to investigate how the Chinese language is used to provide concrete metaphors for abstract moral principles (Liu et al, 2020 ). In the by Shirazi and Talebinezhad ( 2013 ), the subjects discussed a topic in the pretest.…”
Section: Discussionmentioning
confidence: 99%